Protective effect of Shenqi Wenfei Formula against lipopolysaccharide/cigarette smoke-induced COPD in Rat based on gut microbiota and network pharmacology analysis - Shi, Mengyao; Xue, Qian; Xie, Jinghui; Yang, Qinjun; Tong, Jiabing; Zhu, Jie; Gao, Yating; Ma, Xiao; Wu, Di; Li, Zegeng (Frontiers in Microbiology, 2024)
IntroductionThe incidence of chronic obstructive pulmonary disease (COPD) appears to be increasing and evidence suggests that the intestinal flora may play a causative role in its development. Previous studies found that the Shenqi Wenfei Formula (SQWF) can regulate pyroptosis via the NLRP3/GSDMD pathway, thereby reducing the inflammatory response in the lungs of COPD model rats. However, there is no information on whether the drug's effects are associated with intestinal flora. Therefore, this study investigates whether the effects of SQWF are mediated through the regulation of intestinal flora, aiming to elucidate the underlying mechanisms of its therapeutic impact on COPD.MethodsCOPD was induced in rats using lipopolysaccharide and cigarette smoke, followed by intragastric administration of SQWF or physiological saline The targets of SQWF, associated signaling pathways, and key bacterial groups were investigated using 16S rRNA sequencing, network pharmacology, and bioinformatics techniques. The prediction results were validated using quantitative reverse transcription PCR, western blotting, and immunofluorescence, among other methods.ResultsSQWF treatment was found to alleviate COPD in model rats. Treatment was also observed to restore the balance of the intestinal flora in the rats, especially by reducing the abundance of g_Parabacteroides. Bioinformatics predictions identified g_Parabacteroides metabolites, RelA, HDAC1, and enriched neutrophil extracellular trap formation pathways as core targets of SQWF in COPD. qRT-PCR and Western blotting results showed that SQWF treatment reduced ReLA and HDAC1 mRNA and protein expression, along with decreased myeloperoxidase and neutrophil elastase levels in the nucleus.ConclusionTreatment with SQWF was found to restore the imbalance of intestinal g_Parabacteroides in COPD and also regulate the expression of the ReLA and HDAC1 genes, thereby reducing pulmonary neutrophil extracellular traps and alleviating lung inflammation.